Investigating the effects of continuous theta-burst stimulation over the posterior parietal cortex on holistic processing of composite faces: evidence from cognitive modeling - Hanieh Sayadi; Hasan Qarehdaghi; Hamidreza Pouretemad; Jamal Amani Rad (PLoS ONE, 2026)
Efficient interaction with complex visual environments depends on the balance between global and local processing, with a natural tendency to prioritize global information—a phenomenon known as the global advantage. This study investigates how non-invasive brain stimulation using continuous theta-burst stimulation (cTBS) over the posterior parietal cortex (PPC) affects this balance, with a focus on holistic face processing. We conducted a within-subject, crossover, sham-controlled experiment involving 36 participants who completed Navon and composite face tasks before and after cTBS stimulation over the left and right PPC. Cognitive modeling using the Diffusion Model of Conflict (DMC) was employed to examine the cognitive mechanisms involved and compare global and local processing in experimental versus sham conditions. The results confirmed the expected global precedence effect and holistic processing in both tasks but revealed no significant impact of cTBS over the right PPC on task performance in terms of accuracy or response time. However, under incongruent conditions, cTBS over the left PPC led to slower responses to local targets, particularly when compared with the sham condition. Despite these localized effects, no significant changes were observed in composite face task performance following either left or right PPC stimulation. Overall, our findings highlight the complexity of the neural mechanisms governing global-local processing and the limited impact of single-session cTBS over the PPC in altering the cognitive mechanisms underlying these processes. Further research is needed to better understand the role of the PPC in holistic and hierarchical visual processing.